Antibiotic-loaded amphora-shaped pores on a titanium implant surface enhance osteointegration and prevent infections - Ständert, Viviane; Borcherding, Kai; Bormann, Nicole; Schmidmaier, Gerhard; Grunwald, Ingo; Wildemann, Britt (Bioactive materials, 2021)
Artificial prostheses for joint replacement are indispensable in orthopedic surgery. Unfortunately, the implanted surface is attractive to not only host cells but also bacteria. To enable better osteointegration, a mechanically stable porous structure was created on a titanium surface using laser treatment and metallic silver particles were embedded in a hydrophilic titanium oxide layer on top. The laser structuring resulted in unique amphora-shaped pores. Due to their hydrophilic surface conditions and capillary forces, the pores can be loaded preoperative with the antibiotic of choice/need, such as gentamicin. Cytotoxicity and differentiation assays with primary human osteoblast-like cells revealed no negative effect of the surface modification with or without gentamicin loading. An in vivo biocompatibility study showed significantly enhanced osteointegration as measured by push-out testing and histomorphometry 56 days after the implantation of the K-wires into rat femora. Using a S. aureus infection model, the porous, silver-coated K-wires slightly reduced the signs of bone destruction, while the wires were still colonized after 28 days. Loading the amphora-shaped pores with gentamicin significantly reduced the histopathological signs of bone destruction and no bacteria were detected on the wires. Taken together, this novel surface modification can be applied to new or established orthopedic implants. It enables preoperative loading with the antibiotic of choice/need without further equipment or post-coating, and supports osteointegration without a negative effect of the released dug, such as gentamicin.
Gesehen am 07.07.2021